Perlindungan Hukum Terhadap Perempuan Sebagai Korban Kekerasan Dan Diskriminasi - A. A. Sagung Poetri Paraniti; I Wayan Wiryawan (Universitas Mahendradatta, 2020)
Examining a number of issues of violence against women in Indonesialately, has placed women as victims for a very long period of time. This can be seen bythe variation in a number of cases of violence that have implications for all forms ofviolence ranging from physical to intimidation, harassment, humiliation and restrictionof rights as social beings even more visible and organized, namely in the form oftrafficking in women or the coercion of selling themselves. So that women in Indonesiaas a weak group must receive protection. Based on the background of the problemoutlined above, there are several important issues to be discussed further. The problemsare as follows: How is multicomplex legal protection for women as victims of violenceand discrimination, What are the obstacles faced in providing legal protection againstwomen as victims of violence and discrimination. Legal Use Theory. This type ofresearch used in this research is normative legal research which is a scientific researchprocedure to find the truth based on legal scientific logic from the normative side.Violence against women is any action that violates, inhibits, negates the enjoyment andneglect of women's human rights. Based on Komnas Perempuan data, the number ofreported cases of sexual violence in 2017 increased by 74% from 2016. Even in 2019cases of violence against women increased by 14% with a number of 406,178 cases. Theneed for guarantees of protection for women comes along with the awareness to providespecial protection because of the many problems faced by women such as physical andpsychological violence, discrimination, underdevelopment in various fields, and so on.Legal protection for women as victims of violence and discrimination is currentlyregulated in Indonesian law, namely the Criminal Code, Law Number 23 of 2004concerning the Elimination of Domestic Violence, Law Number 21 of 2007 concerningEradication Criminal Acts on Trafficking in Persons, Law Number 39 Year 1999Concerning Human Rights, Presidential Instruction Number 9 Year 2000 concerning Gender Mainstreaming (PUG), Presidential Decree Number 181 Year 1998 concerningthe Formation of the National Commission on Violence against Women or KomnasPerempuan, which was amended by Perpres Number 65 of 2005. Besides that, severalother forms of direct efforts made in providing legal protection for women are throughexisting institutions such as, Integrated Service Centers, and Legal Aid Institutions.There are several obstacles encountered in implementing legal protection againstwomen victims of violence and disks elimination which is caused by several factorsincluding, the substance of the law, law enforcement, culture, facilities and facilities. Forthis reason, there needs to be a number of improvements to a number of components thataffect law enforcement for violence experienced by women, both from human resourceslaw enforcement officers, the establishment of legislation that specifically regulateswomen, and maximizes a number of facilities related to the interests of victims of violenceso that implementation in providing legal protection to women can be properlyaccommodated.